A study on promotion strategy of KTMB Intercity service's in enhancing customer loyalty / Nor Azwa Aminudin - Aminudin, Nor Azwa (Faculty of Business and Management, 2007)
The main purpose of the research is to identify and determine the factors that effect the customer loyalty toward the KTMB Intercity services. Factors such as advertising, sales promotion, personal selling, and publicity have been identified in order to investigate whether or not these factors have significant relationship with customer loyalty. For this study, the questionnaire will be distributed to 50 respondents, taken at Kuala Lumpur Central Station and several other locations such as Gemas Station and Wakaf Bharu Station. Data obtained using two methods that are primary and secondary data. The survey is investigated about the promotion strategy that will enhance customer loyalty whereby the respondents will be asked about the promotion strategy (advertising, sales promotion, personal selling, and publicity) and the recommendation in improving the promotion strategy that have being done by the KTMB Intercity. Once the necessary data has been collected, the data will be analyzed and summarized in a readable and easily interpretable form. The Statistical Package for the Social Science (SPSS) version 12.0 has been used to summarize the data. The results are in the form of reliability testing, frequency, cross tabulation, correlation, and regression analysis. This research found that respondents are still not aware with the products/services offered by KTMB Intercity. They need more promotion on the products/services that offered by KTMB in order to make them familiar with the company's products/services as compete with others transportation company and to increase their loyal customer in the future.